The influence of bronchial asthma control level on the quality of life indices - O. V. Herasymova; T. L. Protsiuk; L. O. Protsiuk; N. M. Surkova; L. D. Kotsur; O. V. Kuleshov (Patologìâ)
Objective: to study the indices of general and specific quality of life in schoolchildren, depending on the level of bronchial asthma control.